Diskriminasi Perempuan Dalam Keluarga Presepektif Hukum Positif dan Al-Qur'an: (Studi Komparatif UU No 23 Tahun 2004 dan Al-Qur’an Surah An-Nisa Ayat 34) - M. Ivan Taufani Faqih; Abdul Syukkur (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Discrimination against women in the family is a problem that is often faced in various aspects of life, including in the context of law and religious teachings. This research aims to compare the perspective of positive law, particularly Law No. 23 of 2004, with the view in the Qur'an, particularly Surah An-Nisa verse 34, regarding the position of women in the family. Law No. 23/2004, which regulates rights and obligations in the family, is often considered to position women in a limited role, potentially reinforcing gender inequality in the family structure. In contrast, Surah An-Nisa verse 34 in the Qur'an provides an understanding of the position of women who should be respected, treated fairly, and given equal rights with men, but still leaves room for different interpretations in society. This research uses a comparative approach to reveal the differences and similarities between the two perspectives in regulating the rights and treatment of women in the family. The results show that although both sources of law have values that prioritize the protection of women, their implementation in practice is often influenced by social and cultural factors that lead to inequality. Therefore, more inclusive legal adjustments and more progressive religious interpretations are needed to achieve gender equality in the family.